Adaptation of some foreign almond cultivars in the ecological conditions of Kahramanmaras province in Turkey - Caglar S.; Kaska N.; Balci S.; Yilmaz K.U. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
Phenological and pomological characteristics and yielding status of nine foreign almond cultivars ('Ferragnès', 'Cristomorto', 'Nonpareil', 'Garrigues', 'Yaltinski', 'Picantili', 'Drake', 'Tuono' and 'Desmayo Largueta') were studied in their 5th and 6th leaves. 'Ferragnès' was found to be the latest flowering cultivar, while 'Desmayo Largueta' was the earliest flowering one. Out of the nine cultivars tested, 'Ferragnès', 'Cristomorto' and 'Tuono' gave the highest yields. Although 'Nonpareil' had the highest kernel percentage, its nut weight was found to be the lowest. 'Picantili' and 'Yaltinski' produced as much as 50 per cent double kernels. 'Ferragnès', 'Tuono' and 'Drake' produced nuts mostly on the spurs, while 'Picantili' only on one-year-old shoots. The late flowering 'Ferragnès', with good yielding performance, appeared to be the best cultivar for the region.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)